The Relationship Between Married Couples’ Knowledge of Anemia Prevention and the Incidence of Anemia Among Pregnant Women - Maesaroh Maesaroh; Qurrat Ul Ain; Yania Febsi; Nisri Ina Zahrah; Nana Fitriana (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2026)
Background: Anemia during pregnancy remains a major public health issue in Indonesia, especially in rural areas such as Tasikmalaya Regency. Limited knowledge and inadequate partner involvement are key factors contributing to poor anemia prevention practices. This study aimed to assess the relationship between couples’ knowledge of anemia prevention and maternal hemoglobin status. Method: A cross-sectional study was conducted among 150 pregnant women and their partners in Tasikmalaya Regency, West Java. Data on sociodemographic characteristics, knowledge, and preventive practices were collected using a structured questionnaire, and hemoglobin (Hb) levels were classified according to WHO (2023) standards. Associations were analyzed using the chi-square test and a multivariate logistic regression. Results: Most respondents were aged 21–35 years (78.7%), and 43.3% had completed secondary education. Although 82% attended ≥4 antenatal care visits and 84.7% reported taking iron (Fe) tablets, the prevalence of anemia remained high at 58.7%, with 26.7% classified as having moderate-to-severe anemia.. A significant association was found between couples’ knowledge and maternal hemoglobin status (χ² = 18.43; df = 6; p = 0.005), with a moderate effect size (Cramér’s V = 0.25). Higher knowledge levels were associated with a greater proportion of non-anemic women, whereas lower knowledge levels were more frequently observed among women with moderate to severe anemia. Conclusion: In Tasikmalaya Regency, higher couples’ knowledge of anemia prevention was significantly associated with better maternal hemoglobin status. These findings support the importance of strengthening couple-based educational approaches and improving the quality of anemia prevention strategies within maternal health programs.